Regenerating Cultural Religious Heritage Intercultural Dialogue on Places of Religion and Rituals - Niglio, Olimpia (Springer Nature Singapore : Imprint: Springer, 2022)
XVII, 288 p. 60 illus., 53 illus. in color.